The use of a co‐design model in improving timely bleed reporting by adults with haemophilia living in the Auckland region of New Zealand. (29th November 2013) - d'Young, A. I.; Young, L.; Ockelford, P. A.; Brasser, M.; Slavin, K.; Manson, L.; Preston, S.
Summary Many adult patients diagnosed with phenotypically moderate and severe haemophilia living in the Auckland region of New Zealand do not report bleeding episodes within a timeframe that allows for optimal assessment and management. This can result in poor clinical outcomes for patients and poor oversight of the use of expensive clotting factor concentrates. Our goal was to improve both the number and speed at which bleeding episodes were reported to our centre, improving access to care and clinical oversight of the use of expensive factor concentrates and aiding the development of a care partnership with patients. We worked with 70 adult PWH living in the Auckland region of New Zealand with moderate and severe haemophilia A and B. Over a 5‐month period between March and July 2013 we used a co‐design model to develop and implement a range of strategies to improve the timing and frequency of bleed reporting. Mean bleed reporting time was reduced threefold, with a threefold increase in the number of bleeds reported per month. We reduced the number of bleeding episodes reported outside of a prespecified 48‐h time limit by 68%. We significantly improved bleed reporting and time to report, indicating improved access to our services, improved clinical oversight and improved accountability to our national funder. We have achieved a care partnership and a reduction in factor consumption for the study population without compromising the quality of care they receive.